Effect of different methods of hygiene on the color stability of extrinsically pigmented facial silicone - Cabral, Yasmin Morais; Pesqueira, Aldiéris Alves [UNESP]; Moreno, Amália; Goiato, Marcelo Coelho [UNESP]; Haddad, Marcela Filié (Universidade Estadual de Campinas, 2018)
Aim: Evaluate the color stability of facial silicone pigmented extrinsically under the influence of the hygiene process. Methods: 160 samples were prepared and divided into 8 groups (n = 20) according to the pigmentation technique used: Group 1: Colorless silicone; Group 2: Pigmented exclusively with oil ink; Group 3: Pigmented with oil ink + opacifier; Group 4: Colorless, applying Prime; Group 5: Pigmented with oil ink covered with Prime; Group 6: Pigmented with oil ink + opacifier and covered with Prime; Group 7: Pigmented with oil ink diluted in Prime; Group 8: Pigmented with oil ink + opacifier diluted in Prime. Then the samples were distributed into two subgropus (n=10): 1: neutral soap and 2: 1% hypochlorite solution. The color readings occurred in the initial period and 60 days after the hygiene procedures. For this, it was used a spectrophotometer reflection and CIE-Lab program. The data was tabulated and submitted to analysis of variance (ANOVA) followed by Tukey test (p < 0.05). Results: The groups of samples disinfected with soap showed significantly lower color change values than those presented by the samples disinfected with hypochlorite. The best results were presented by the group of samples pigmented with oil ink diluted in prime and sanitized with neutral soap (ΔE=1.21, without opacifier and ΔE=0.82, with opacifier). Conclusions: The association of oil ink diluted in prime and hygiene technique with soap promotes the lower color change of facial silicone pigmented extrinsically.
Keywords: Disinfection; Maxillofacial prosthesis; Prosthesis coloring